Supportive Educative System Intervention Based On The Integration Of Self Care And Family Centered Nursing Model On Family Support In Improving The Nutritional Status Of Tuberculosis Patients - weti; Fatsiwi Nunik Andari; Liza Fitri Lina; Bintang Agustina Pratiwi (Institut Citra Internasional, 2025)
Malnutrition and tuberculosis (TB) are interconnected or interconnected problems. Malnutrition in TB patients is one of them influenced by lack of family support for TB patients, both in emotional, appreciative, instrumental, and informational support. The purpose of this study is to evaluate the influence of supportive educational system interventions in improving family support. This research method is quantitative with a quasi experimental design, in two health centers, namely Kandang Mas and Betungan, consisting of 48 respondents who were divided into 2 groups, namely the control group, given the standard intervention of the health center (n=24) and the treatment group, given the standard intervention of the health center and the supportive educative system (n=24). The data were analyzed using the two-way anova test. The results showed that the family development stage and the interaction between the family development stage and the intervention group did not affect family support (p > 0.05). Meanwhile, the supportive educative system intervention had a negative effect on family support in improving the nutritional status of TB patients (p = 0.015, mean = 76.52), however, the supportive educative system intervention had a positive effect on instrumental support in the treatment group (p = 0.029, mean = 81.19). Conclusion of this study is that the supportive educative system intervention is not more effective than the standard intervention of the health center, this can occur due to the influence of sample characteristics, research time, and control of variables and other factors that also affect the results of the study.